Indigenous Communities: A Way of Living that puts the Earth Charter into Practice - Ovares-Barquero, Sandra (2016)
This paper aims to draw attention to the role that indigenous communities have historically fulfilled by practicing the values proposed in the Earth Charter upon its ancestral construction. The intention is to reflect on the fact that the principles stated in the Earth Charter have been intrinsically performed by these groups on a daily basis. That is, these groups become a role model because they respect life in all its diverse forms, promoting a democratic, participative, sustainable, and peaceful existence, which ensures, the balance of Earth to present and future generations. On the other hand, this paper analyzes the damage caused by human beings, through their unfriendly practices, to Latin American natural resources and therefore to the planet. Moreover, the human species is the only one able to reverse the damage caused. Based on this context, the hope is to place the human being as the center of the planetary system. This requires an education that raises awareness and contributes to the overall view of the problems and takes into account their short, medium, and long term consequences, not only for a community but also for the entire humankind.